Lower Bounds on Solutions of Quadratic Polynomials Defined over Finite Rings - Ali H. Hakami (International Journal of Mathematics and Mathematical Sciences)
Let m be a positive integer and let Rm denote the ring Z/(m), and let Rmn denote the Cartesian product of n copies of Z/m. Let f(x) be a quadratic polynomial in Z[x1,…,xn]. In this paper, we are interested in giving lower bounds on the number of solutions of the quadratic polynomial f over the ring Rmn.